Human ETS2 gene on chromosome 21 is not rearranged in Alzheimer disease. - Sacchi, N (1988)
The human ETS2 gene, a member of the ETS gene family, with sequence homology with the retroviral ets sequence of the avian erythroblastosis retrovirus E26 is located on chromosome 21. Molecular genetic analysis of Down syndrome (DS) patients with partial trisomy 21 allowed us to reinforce the supposition that ETS2 may be a gene of the minimal DS genetic region. It was originally proposed that a duplication of a portion of the DS region represents the genetic basis of Alzheimer disease, a condition associated also with DS. No evidence of either rearrangements or duplications of ETS2 could be detected in DNA from fibroblasts and brain tissue of Alzheimer disease patients with either the sporadic or the familiar form of the disease. Thus, an altered ETS2 gene dosage does not seem to be a genetic cause or component of Alzheimer disease.